Ectopic Thymic Cyst of the Subglottis: Considerations for Diagnosis and Management. (March 2018) - Ahmad, Iram; Kirby, Patricia; Liming, Bryan
Objectives: To share the diagnostic and management challenges created by an extremely rare airway lesion—the subglottic ectopic thymic cyst. Study Design: Case report and literature review. Methods: We review the presentation, management, and clinical course of an infant who presented with a subglottic mass that was histologically confirmed as a thymic cyst. A brief literature review supplements the case presentation Results: We present the third described case of an ectopic thymic cyst presenting as a subglottic mass. The differential diagnosis of subglottic masses in neonates consists primarily of subglottic hemangioma and mucous retention cysts. Otolaryngologists must be prepared for unexpected findings when dealing with critical airways. We compare the presentation and management of our patient with the 2 previously described cases. We propose an embryologic theory for the origin of these rare lesions. Conclusions: An ectopic thymic cyst is a rare and unexpected cause of neonatal stridor. Management of pediatric airway lesions must allow for unexpected findings at the time of diagnostic and therapeutic endoscopy. The appropriate management of subglottic thymic cysts is poorly defined, but close surveillance for recurrence is mandatory.